Two Problems of Concentration in Serbian Banking Sector - Ljumović, Isidora Lj; Pavlović, Vladan; Cvijanović, Janko M (Industrija, 2014)
This paper aims to approach concentration in the banking industry from two perspectives. Broader analysis shows that capital markets are underdeveloped and that Serbian financial system is bank based. Analysing the concentration from narrow perspective, authors concluded that the banking sector in Serbia is characterized as a highly fragmented, but the reduction of the number of banks did not lead to an increase in the concentration of any of the analysed parameters and the level of concentration is moderately low. Detail analysis of selected counties was performed as comparative analysis. Unfortunately, it was impossible to make a universal conclusion about whether reducing the number of banks affect positively or negatively the degree of concentration.
Keywords: Capital; Analysis; Concentration ratio; Herfindahl-Hirschman Index; Bank consolidation; Bank-based systems; Bank concentration